Parvovirus B19 DNAemia in pregnant women in relation to perinatal death: A nested case‐control study within a large population‐based pregnancy cohort. (28th January 2020) - Barlinn, Regine; Trogstad, Lill; Rollag, Halvor; Frøen, Fredrik; Magnus, Per; Dudman, Susanne G.
Abstract: Introduction: Parvovirus B19 (B19V) is the infectious cause of exanthema infectiosum. In Europe around 40% of pregnant women are susceptible to infection. Having small children at home is the main risk factor for contracting an infection during pregnancy. The association between B19V‐infection and perinatal death is not yet settled. The aims of the study were to estimate the association between maternal parvovirus B19 infection in pregnancy and perinatal death, and to assess the significance of a positive B19V PCR in pregnancy. Material and methods: The study population consists of women included in the Norwegian Mother and Child Cohort Study, a prospective population‐based pregnancy cohort of nearly 100 000 women. Blood samples were obtained during weeks 17‐18 in pregnancy (M1), at birth, and in umbilical cord blood. Within participants in the pregnancy cohort, 138 cases of perinatal death and 1350 controls with live‐born children were included in a nested case‐control study. Samples were analyzed with B19V serology and B19V PCR according to a predefined test algorithm. For cases, medical records and laboratory results from hospitals were combined with the results of B19V serology and PCR. The reported causes of perinatal death were categorized using the classification system: Causes Of Death and Associated Conditions (CODAC). Results: The B19V seroconversion rates were 9.8% for cases and 6.8% for control mothers. The odds ratio for maternal B19V infection in cases compared with controls was 1.28 (95% CI 0.35‐4.70), adjusted for age, parity, body mass index and tobacco use. B19V‐PCR‐positive samples were detected at weeks 17‐18 of gestation in both cases and controls. The proportion of positive samples was similar in cases and controls, 24% and 28.2%, respectively. Mothers with PCR‐positive M1 samples transmitted B19V vertically in 9.1% of cases and in 11.9% of the controls. Of all perinatal deaths, 53% were attributed to placental pathology or unknown causes. Conclusions: B19V PCR positivity was high and similar in both cases and controls. In our study B19V DNAemia was not seen to be associated with fatal outcome of pregnancy. The clinical significance of B19V DNA detection during pregnancy is uncertain. Caution is needed when diagnosing a B19V infection based only on B19V DNAemia.